Penerapan model cooperative script untuk meningkatkan hasil belajar matematika - Diyan Rusydiana (Indonesian Journal of Educational Development, 2021)
This study aims to describe the implementation of the Cooperative Script Learning Model to improve the mathematics learning outcomes of class X MIPA 1 students of SMA Negeri 1 Kedunggalar Ngawi in the 2016/2017 Academic Year. In this research, the problem statement is “how the implementation of Cooperative Script learning improves the learning outcomes of the Mathematics Absolute Value Equation of class X MIPA 1 students of SMA Negeri 1 Kedunggalar Ngawi?” The research conducted is a Classroom Action Research, where the teacher applies the learning model and the researcher makes observations based on the aspecs in the learning model. The respondents of this study were 26 students of class X MIPA 1 of SMA Negeri 1 Kedunggalar in the 2016/2017 Academic Year. Data were collected using tests. The researcher gave a test at the end of the lesson. The data were analyzed after obtaining data on student learning outcomes before and after using the action. The data analysis technique used is descriptive statistical analysis. The indicators of success in this study are the improvement of students mathematics learning outcomes, with individual completeness ≥ 70 from the KKM determined by the school and classical completeness ≥ 75% of the total students who reach the KKM. The completeness analysis based on the scores acquired by students before the action obtained classical results with an average 50%. Meanwhile, after the action , the result was obtained as follows : Cycle I was 65.38% and Cycle II was 76.92%. Based on the results of the study, from the action analysis, it was concluded that the application of the Cooperative Script learning model can improve the learning outcomes of the absolute value equation of mathematics for class X MIPA1 SMA Negeri 1 Kedunggalar. This can be seen from the study completeness analysis of class X MIPA 1 students of SMA Negeri 1 Kedunggalar Ngawi after the action. Acording to the analysis result of the individual completeness of 26 students, it was found that 20 students had completed and 6 students had not, with average completeness of 73.65%. Penelitian ini bertujuan untuk mendiskripsikan penerapan model pembelajaran Cooperative Script dalam upaya meningkatkan hasil belajar matematika siswa kelas X MIPA 1 Tahun Pelajaran 2016/2017 SMA Negeri 1 Kedunggalar Ngawi. Dalam penelitian ini rumusan masalahnya “Bagaimana Penerapan Pembelajaran Cooperative Script dapat Meningkatkan Hasil Belajar Persamaan Nilai Mutlak Matematika Siswa Kelas X MIPA 1 SMA Negeri 1 Kedunggalar Ngawi?” Penelitian yang dilakukan merupakan Penelitian Tindakan Kelas, yaitu dimana guru yang menerapkan model pembelajaran dan peneliti yang melakukan observasi berdasarkan aspek yang terdapat dalam model pembelajaran yang digunakan. Siswa kelas X MIPA 1 Tahun Pelajaran 2016/2017 SMA Negeri 1 Kedunggalar yang berjumlah 26 orang, dijadikan responden dalam penelitian ini. Pengambilan data dilakukan dengan menggunakan tes. Peneliti memberikan tes di akhir pembelajaran. Setelah diperoleh data hasil belajar siswa sebelum dan setelah menggunakan tindakan, kemudian data dianalisis. Teknik analisis data yang digunakan adalah analisis statistik deskriptif. Adapun indikator keberhasilan dalam penelitian ini adalah meningkatnya hasil belajar matematika siswa, dengan ketuntasan individual ≥ 70 dari KKM yang ditentukan sekolah dan ketuntasan klasikal ≥ 75% dari jumlah siswa yang mencapai KKM. Analisis ketuntasan berdasarkan skor yang diperoleh siswa sebelum tindakan, diperoleh hasil secara klasikal dengan rata-rata 50% sedangkan setelah tindakan diperoleh hasil sebagai berikut: Siklus I adalah 65.38% dan siklus II adalah 76.92%. Berdasarkan hasil penelitian, dari analisis tindakan, diperoleh kesimpulan bahwa penerapan model pembelajaran Cooperative Script dapat meningkatkan hasil belajar persamaan nilai mutlak matematika siswa kelas X MIPA 1 SMA Negeri 1 Kedunggalar. Hal ini dapat dilihat dari analisis ketuntasan belajar siswa kelas X MIPA 1 SMA Negeri 1 Kedunggalar setelah tindakan. Berdasarkan hasil analisis ketuntasan individual dari 26 siswa, diperoleh 20 siswa tuntas dan 6 siswa yang belum tuntas, dengan rata-rata ketuntasan adalah 73.65%.